P-wave electron-Be^3+, C^5+, and O^7+ elastic scattering and photoabsorption in two-electron systems - Bhatia, Anand K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
In previous papers [Bhatia, Phys. Rev. A 85, 052708 (2012); 86, 032709 (2012); 87, 042705 (2013)] electron-hydrogen, electron-He+, electron-Li2+ P-wave scattering phase shifts were calculated using the variational polarized orbital theory. This method is now extended to the singlet and triplet P-wave scattering from Be3+, C5+, and O7+ in the elastic region. The long-range correlations are included in the Schrödinger equation by using the method of polarized orbitals variationally. Phase shifts are compared to those obtained by other methods. The present calculation provides results which are rigorous lower bonds to the exact phase shifts. Using the presently calculated P-wave continuum functions, photoionization of the singlet and triplet S states of Be2+, C4+, and O6+ are also calculated, along with the radiative recombination rate coefficients at various electron temperatures.